Pemberdayaan Perempuan melalui Pengembangan Usaha Minuman Tradisional Wedang Uwuh di Desa Muntuk, Dlingo, Bantul, Yogyakarta - Tanto Lailam; Awang Daru Murti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The focus of community service is the empowerment of women through the business development of wedang uwuh traditional beverage. Wedang uwuh is a traditional beverage that is famous among the people of the Special Region of Yogyakarta. Wedang uwuh is a hot or warm beverage that has a sweet and spicy taste with bright red and fragrant aroma. This community service is motivated by the problems: the wedang uwuh business does not yet have a permit for household industrial products (PIRT), the manager does not understand how to market and make branding of wedang uwuh, wedang uwuh does not have packaging that fits the market target tourism, and others. To overcome this problem, in this service a variety of wedang uwuh business development activities were carried out: (1) efforts to manage PIRT permits, product marketing, and branding communication training, marketing training via social media, wedang uwuh packing training, and facilitation of business development tools and appropriate packaging tourist target